ANALYSIS TECHNOLOGY ACCEPTANCE MODEL (TAM) TERHADAP ACCEPTANCE OF PERANGKAT LUNAK AKUNTANSI (AOP) MENYONGSONG ASEAN ECONOMIC COMMUNITY (AEC) 2015 - Eni Dwi Susliyanti (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2015)
This study aims to analyze student perception of accounting software skill using Technology Acceptance Model (TAM) preparing ASEAN Economic Community (AEC 2015). This study will analyze significant influence between Perceived Ease of Use (PEU) with Perceived Usefulness (PU), Perceived Ease of Use (PEU) with Attitude Towards Usage (ATU), PEU with Acceptance of PLA (AoP), PU and ATU with Acceptance of PLA (AoP), AoP with AEC 2015. This study uses survey method with 100 accounting students. The data analyzed using SmartPLS 3.1 statistical software. The results show there is significant influence between PEU with PU, PE with ATU, PU with AOP, AOP with AEC and there isn’t significant influence between PEU with ATU and PEU with AOP. Keywords: TAM, PLA, PEU, PU, ATU, AOP, AEC 2015